Women’s Role in Watershed Management - Novlloyd Celeste (New Advances in Business, Management and Economics Vol. 7, 2025)
In this study, the roles of women in watershed management in the Calbayog Pan-as Hayiban Protected Landscape (CPHPL) in Calbayog City are identified to add to the expanding scientific body of information regarding women’s participation in watershed protection. A systematic literature review was conducted using the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) and Scopus databases (for example, Science Direct). Data on Payment for Ecosystem Services in Calbayog City were used for willingness-to-pay analysis. A documentary review by the Protected Area Management Board (PAMB) was conducted to highlight women’s participation in the watershed management and planning process. This study reveals that women are highly acknowledged and part of the planning process as representatives of their respective organisations. The decision of women to protect the watershed relies on the will of a political leader. On the other hand, women are hampered in their participation in watershed management because of the socio-cultural and institutional context. Moreover, from the WTP of women, it appears that the number of years of residency, age, bid amount offered, knowledge of watershed, and the perception that watershed is important in water supply are factors that affect their WTP.